Świadomość studentów na temat występowania i żerowania kleszczy w Polsce = Student’s awareness about appearance and feeding of ticks in Poland - Kowalczyk, Anna; Kozłowska, Ewelina; Pacian, Anna; Skórzyńska, Hanna (Journal of Education, Health and Sport, 2015)
Kowalczyk Anna, Kozłowska Ewelina, Pacian Anna, Skórzyńska Hanna. Świadomość studentów na temat występowania i żerowania kleszczy w Polsce = Student’s awareness about appearance and feeding of ticks in Poland. Journal of Education, Health and Sport. 2015;5(9):469-480. ISSN 2391-8306. DOI10.5281/zenodo.31176 http://dx.doi.org/10.5281/zenodo.31176 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A469-480 https://pbn.nauka.gov.pl/works/628573 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 15.09.2015. Świadomość studentów na temat występowania i żerowania kleszczy w Polsce Student’s awareness about appearance and feeding of ticks in Poland Anna Kowalczyk1, Ewelina Kozłowska2, Anna Pacian3, Hanna Skórzyńska3 1. Studenckie Koło Naukowe Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Samodzielna Pracownia Epidemiologii, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3. Katedra Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Autor do korespondencji / Author for correspondence lic. Anna Kowalczyk e-mail: annakowalczyklublin@gmail.com Streszczenie Wprowadzenie. Kleszcze to jedne z najbardziej niebezpiecznych zewnętrznych pasożytów człowieka. Bytują one głównie w lasach liściastych i mieszanych lub otaczających je miejscach o bogatej roślinności. Pod wpływem zachodzących zmian obszar ich występowania uległ znacznemu poszerzeniu. Wędrując w kierunku potencjalnych żywicieli dotarły i zaklimatyzowały się nie tylko na terenach wiejskich, ale także w miejskich parkach, ogrodach czy skwerach. Cel badań. Zbadanie świadomości studentów kierunków przyrodniczych na temat występowania i żerowania kleszczy w Polsce. Materiał i metoda. Badanie przeprowadzono wśród 184 studentów Uniwersytetu Przyrodniczego w Lublinie, w okresie od V – VI 2014 roku. Zastosowaną metodą badawczą był sondaż diagnostyczny przeprowadzony techniką ankietowania. Wyniki. Zaledwie co piąty student wiedział, iż najwięcej kleszczy w lesie występuje w okolicach ścieżek. Aby mogły przeżyć potrzebują krwi żywiciela, wiedziało o tym ponad 78% ankietowanych. Jedynie 22% studentów było świadomych tego, iż każda forma rozwojowa kleszczy stanowi potencjalne zagrożenie dla człowieka. Prawidłowe postępowanie w przypadku ukąszenia przez kleszcza potrafiło opisać 58% ankietowanych. Wnioski. Świadomość studentów na temat występowania i żerowania kleszczy w Polsce kształtuje się na średnim poziomie. Nakazuje to zarówno kontynuowanie istniejących działań edukacyjnych w zakresie środowiskowych zagrożeń zdrowia, jak i podejmowanie nowych inicjatyw w celu kształtowania kompleksowej wiedzy i umiejętności niezbędnych do ochrony przed zagrożeniami. Słowa kluczowe: studenci, świadomość, zagrożenia środowiskowe, kleszcze. Abstract Introduction. Ticks are the most dangerous human external parasites. They live mainly in deciduous and mixed coniferous forests or in places surrounded by rich flora. Under the influence of changes their area of appearance significantly expanded. Wandering towards potential hosts they reached and acclimatized not only on country areas, but also in municipal parks, gardens and squares. Research Aim. An aim of research is to examine student’s awareness from the faculty of sciences about appearance and feeding of ticks in Poland. Material and Method. Examination was conducted amongst 184 students of the University of Life Sciences in Lublin, in a period of 05-06.2014. Diagnostic survey method was conducted surveys technique. Results. Only every fifth student knew that most ticks in the forest can be found in surroundings of paths. Over 78% of respondents knew that ticks in order to survive need a blood of the host. Only 22% of students were aware of the fact that every developmental form of ticks creates a threat to the man. Proper behavior in case of tick bite was able to describe 58% of respondents. Conclusions. Student’s awareness about appearance and feeding of ticks in Poland develops on an average level. This requires both the continuation of existing educational activities in the field of environmental health threats, and new initiatives in order to gain a comprehensive knowledge and essential abilities to protection against threats. Key words: students, awareness, enviromental risks, ticks.